Surface protection film

KR1020260140248APending Publication Date: 2026-09-22NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020267026444
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-01-15
Filing Date
2025-01-09
Publication Date
2026-09-22

Smart Images

  • Figure PCT00008_ABST
    Figure PCT00008_ABST
Patent Text Reader

Abstract

The present invention provides a surface protection film comprising an adhesive layer, capable of exhibiting sufficient strong adhesion to a substrate before UV irradiation, excellent peelability that allows for smooth peeling from the substrate after UV irradiation, and excellent storage stability. The surface protection film according to an embodiment of the present invention is a surface protection film comprising an adhesive layer, wherein the adhesive constituting the adhesive layer is formed as an adhesive composition, and the adhesive composition comprises a urethane prepolymer (A), a crosslinking agent (B), a photopolymerization initiator (C), and an antioxidant (D), wherein the urethane prepolymer (A) comprises an alkylene oxide backbone comprising two of at least one group selected from the group consisting of methylene groups and methine groups, and an alkylene oxide backbone comprising three or more of at least one group selected from the group consisting of methylene groups and methine groups.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a surface protection film. Background Technology

[0002] In the manufacturing process of optical or electronic devices, a surface protection film is generally applied to the exposed surface of the optical or electronic component to prevent scratches from occurring on the surface of the optical or electronic component during processing, assembly, inspection, transportation, etc. This surface protection film is peeled off from the optical or electronic component when the need for surface protection is no longer present (Patent Document 1).

[0003] For surface protection films attached to the exposed surfaces of such optical or electronic components, it is necessary to exhibit sufficient strong adhesion so that they do not peel off easily while surface protection is required. On the other hand, when surface protection is no longer needed, excellent peelability is required to smoothly peel off the surface protection film without contamination or damage to the optical or electronic components. In other words, a combination of sufficient strong adhesion while surface protection is required and excellent peelability when surface protection is no longer needed is required.

[0004] As a technique for adjusting adhesive strength, a surface protection sheet for optical components in which adhesive strength is reduced by irradiating with ultraviolet rays has been reported (Patent Document 2). Additionally, a surface protection sheet for optical components in which adhesive strength is reduced by irradiating with ultraviolet rays to exhibit light peelability has been reported (Patent Document 3). However, the adhesive reported in Patent Document 2 cannot sufficiently increase adhesive strength before ultraviolet irradiation, nor can it sufficiently decrease adhesive strength after ultraviolet irradiation. Furthermore, the adhesive reported in Patent Document 3 cannot sufficiently decrease adhesive strength. For this reason, the compatibility of sufficient strong adhesive strength while surface protection is required and excellent light peelability at the point when surface protection is no longer required has not been achieved.

[0005] As another technique for adjusting adhesive strength, an adhesive obtained by adding a specific radical polymerizable monomer containing (meth)acryloyl groups and active hydrogen groups to a specific urethane prepolymer has been reported (Patent Document 4). However, the adhesive reported in Patent Document 4 has a problem in that it has low adhesive strength before UV irradiation, and is prone to peeling off while surface protection is required.

[0006] As another technique for adjusting adhesive strength, an adhesive obtained from an adhesive composition obtained by adding a polyfunctional (meth)acrylate to a urethane prepolymer having two or more hydroxyl groups and (meth)acryloyloxy groups has been reported (Patent Document 5). However, the adhesive reported in Patent Document 5 also has a problem in that the adhesive strength is low before UV irradiation, and it is prone to peeling off while surface protection is required.

[0007] In addition, conventional adhesives as listed above have a problem in that their adhesive performance deteriorates during storage. Prior art literature

[0008] Japanese Patent No. 6613516, Japanese Patent Publication No. 2019-116609, Japanese Patent Publication No. 2019-116610, Japanese Patent No. 6769503, Japanese Patent No. 7285072 The problem to be solved

[0009] The objective of the present invention is to provide a surface protection film comprising an adhesive layer, the primary purpose of which is to be adhered to an exposed surface to prevent scratches on the surface of an optical or electronic component during processing, assembly, inspection, transportation, etc., in a manufacturing process of an optical or electronic device, the surface protection film is capable of exhibiting sufficient strong adhesion to a substrate before UV irradiation, excellent light peelability that allows for smooth peeling from the substrate after UV irradiation, and also has excellent storage stability. Furthermore, the invention is to provide an optical device and an electronic device comprising such a surface protection film. means of solving the problem

[0010] [1] A surface protection film according to an embodiment of the present invention is a surface protection film comprising an adhesive layer, wherein the adhesive constituting the adhesive layer is formed as an adhesive composition, and the adhesive composition comprises a urethane prepolymer (A), a crosslinking agent (B), a photopolymerization initiator (C), and an antioxidant (D), and the urethane prepolymer (A) comprises an alkylene oxide backbone comprising two groups selected from the group consisting of methylene groups and methine groups, and an alkylene oxide backbone comprising three or more groups selected from the group consisting of methylene groups and methine groups.

[0011] [2] In the surface protection film described in [1] above, the amount of the antioxidant (D) per 100 parts by weight of the urethane prepolymer (A) may be 0.10 parts by weight or more.

[0012] [3] In the surface protection film described in [1] or [2] above, the ratio of the amount of antioxidant (D) to the amount of photopolymerization initiator (C) (antioxidant (D) / photopolymerization initiator (C)) may be 0.25 or more by weight.

[0013] [4] In the surface protection film described in any one of [1] to [3] above, the ratio of the amount of antioxidant (D) to the amount of photopolymerization initiator (C) (antioxidant (D) / photopolymerization initiator (C)) may be less than 3.00 in weight ratio.

[0014] [5] In the surface protection film described in any one of [1] to [4] above, the amount of the photopolymerization initiator (C) per 100 parts by weight of the urethane prepolymer (A) may exceed 0.1 parts by weight.

[0015] [6] In the surface protection film described in any one of [1] to [5] above, the adhesive composition may include urethane (meth)acrylate.

[0016] [7] An optical device according to an embodiment of the present invention comprises a surface protection film described in any one of claims [1] to [6].

[0017] [8] An electronic device according to an embodiment of the present invention includes a surface protection film described in any one of claims [1] to [6]. Effects of the invention

[0018] According to the present invention, a surface protection film comprising an adhesive layer is provided, which is primarily intended to be adhered to an exposed surface to prevent scratches on the surface of an optical member or an electronic member during processing, assembly, inspection, transportation, etc., in a manufacturing process of an optical device or an electronic device. The surface protection film can exhibit sufficient strong adhesion to a substrate before UV irradiation, excellent light peelability that allows it to be smoothly peeled off from the substrate after UV irradiation, and also has excellent storage stability. Furthermore, an optical device and an electronic device comprising such a surface protection film can be provided. Brief explanation of the drawing

[0019] FIG. 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. Specific details for implementing the invention

[0020] Where the term "weight" appears in this specification, it may be replaced with "mass," which is the SI unit commonly used to represent weight.

[0021] In this specification, where the expression “(meth)acryl” is used, it means “acryl and / or methacryl”; where the expression “(meth)acrylate” is used, it means “acrylate and / or methacrylate”; where the expression “(meth)acryloyl” is used, it means “acryloyl and / or methacryloyl”; where the expression “(meth)allyl” is used, it means “allyl and / or metallyl”; and where the expression “(meth)acrolein” is used, it means “acrolein and / or methacryloyl”.

[0022] ≪≪A. Surface Protection Film≫≫

[0023] A surface protection film according to an embodiment of the present invention includes an adhesive layer. The adhesive layer may be an adhesive layer consisting of only one layer, or an adhesive layer consisting of two or more layers.

[0024] A surface protection film according to an embodiment of the present invention may include an adhesive layer, and may include any other suitable layer (component) within a range that does not impair the effects of the present invention. Such other layers may be one layer or two or more layers. Examples of such other layers include a substrate layer and a release liner (also referred to as a release sheet or separator). Typically, the surface protection film of the present invention includes a substrate layer and an adhesive layer.

[0025] FIG. 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. In FIG. 1, the surface protection film (10) comprises a substrate layer (1) and an adhesive layer (2). In FIG. 1, the substrate layer (1) and the adhesive layer (2) are directly laminated. In FIG. 1, any suitable release liner (also referred to as a release sheet or separator) may be provided on the surface of the adhesive layer (2) opposite to the substrate layer (1) for protection until use (not shown).

[0026] As described above, a surface protection film according to one embodiment of the present invention has a laminated structure in which a substrate layer, an adhesive layer, and a release liner are laminated in that order, and the release liner is the outermost layer. A surface protection film according to another embodiment of the present invention has a laminated structure in which a substrate layer and an adhesive layer are laminated in that order, and the adhesive layer is the outermost layer.

[0027] The thickness of the surface protection film according to an embodiment of the present invention is preferably 5 μm to 500 μm, may be 10 μm to 450 μm, may be 15 μm to 400 μm, and may be 20 μm to 300 μm.

[0028] A surface protection film according to an embodiment of the present invention has an adhesive layer included in the surface protection film bonded to the surface of a glass plate, and after being left for 30 minutes in an environment of 23°C and 55%RH humidity, the adhesive strength (hereinafter referred to as "initial adhesive strength before UV irradiation against the glass plate") when the surface protection film is peeled from the surface of the glass plate at a peeling angle of 180 degrees and a peeling speed of 300 mm / min in an environment of 23°C and 55%RH humidity is preferably 100 gf / 25 mm or more, may be 300 gf / 25 mm or more, may be 500 gf / 25 mm or more, may be 1000 gf / 25 mm or more, may be 1300 gf / 25 mm or more, may be 1500 gf / 25 mm or more, may be 1800 gf / 25 mm or more, or may be 2000 gf / 25 mm or more. It may be above. The higher the initial adhesion strength before UV irradiation of the glass plate, the better; however, if it is excessively high, there is a risk that sufficient light peelability may not be achieved even after UV irradiation. Therefore, as an upper limit value, for example, 5000 gf / 25 mm or less is preferable, and it may be 4000 gf / 25 mm or less, or 3500 gf / 25 mm or less. If the initial adhesion strength before UV irradiation of the glass plate is within the above range, the surface protection film according to the embodiment of the present invention can exhibit sufficient strong adhesion strength to, for example, a substrate. If the initial adhesion strength before UV irradiation of the glass plate is too low and falls outside the above range, there is a risk that the surface protection film will peel off from the substrate while surface protection is required. Furthermore, details of the method for measuring the initial adhesion strength before UV irradiation of the glass plate will be described later.

[0029] A surface protection film according to an embodiment of the present invention is formed by bonding an adhesive layer included in the surface protection film to the surface of a glass plate and irradiating it with ultraviolet light having an integrated light intensity of 700 mJ / cm² by an LED light source with a wavelength of 365 nm, and then leaving it for 30 minutes in an environment of a temperature of 23°C and a humidity of 55%RH, and then peeling the surface protection film from the surface of the glass plate at a peeling angle of 180 degrees and a peeling speed of 300 mm / min in an environment of a temperature of 23°C and a humidity of 55%RH, wherein the adhesive strength (hereinafter referred to as "initial adhesive strength after UV irradiation against the glass plate") is preferably 20.00 gf / 25 mm or less, may be 16.00 gf / 25 mm or less, may be 12.00 gf / 25 mm or less, may be 10.00 gf / 25 mm or less, or may be 8.00 gf / 25 mm It may be less than 7.00 gf / 25 mm, less than 6.00 gf / 25 mm, less than 5.50 gf / 25 mm, or less than 5.00 gf / 25 mm. The lower the initial adhesive strength after UV irradiation of the glass plate, the better; however, if it is excessively low, there is a risk that it may naturally peel off from the substrate in unintended circumstances. Therefore, as a lower limit value, for example, 1.00 gf / 25 mm or more is desirable, and it may be 1.50 gf / 25 mm or more. If the initial adhesive strength after UV irradiation of the glass plate is within the above range, the adhesive strength is very low, so the surface protection film according to the embodiment of the present invention can be peeled off smoothly without contamination or damage to the substrate, for example, when it is necessary to peel it off from the substrate. If the initial adhesion strength after UV irradiation of the glass plate exceeds the above range and is too high, there is a risk of contamination or damage to the substrate when attempting to peel it off. Furthermore, details regarding the method for measuring the initial adhesion strength after UV irradiation of the glass plate will be described later.

[0030] The surface protection film according to an embodiment of the present invention has a ratio of change in initial adhesive strength before UV irradiation of the glass plate to the initial adhesive strength after UV irradiation of the glass plate (initial adhesive strength before UV irradiation of the glass plate / initial adhesive strength after UV irradiation of the glass plate) (ratio) (which may be referred to as "ratio of change in initial adhesive strength before / after UV irradiation of the glass plate") preferably 5 times or more, may be 10 times or more, may be 100 times or more, may be 200 times or more, may be 300 times or more, and may be 400 times or more. The higher the ratio of change, the better, but considering ease of handling, the upper limit is preferably 10,000 times or less, may be 5,000 times or less, may be 2,000 times or less, may be 1,500 times or less, and may be 1,000 times or less. If the above change ratio is within the above range, for example, the effects of the present invention can be further expressed, a more sufficient strong adhesion force can be expressed to the substrate, and when it is necessary to peel from the substrate, a more excellent peelability can be expressed so that it can be peeled more smoothly from the substrate.

[0031] A surface protection film according to an embodiment of the present invention, after manufacturing the surface protection film, stores it under a fluorescent lamp for one day in an environment of 23°C and 55%RH humidity, bonds an adhesive layer included in the surface protection film to the surface of a glass plate, leaves it for 30 minutes in an environment of 23°C and 55%RH humidity, and then peels the surface protection film from the surface of the glass plate at a peeling angle of 180 degrees and a peeling speed of 300 mm / min in an environment of 23°C and 55%RH humidity; the adhesive strength (hereinafter referred to as "initial adhesive strength before UV irradiation of the glass plate after storage under a fluorescent lamp for one day") is preferably 100 gf / 25 mm or more, may be 300 gf / 25 mm or more, may be 500 gf / 25 mm or more, may be 1000 gf / 25 mm or more, or may be 1300 gf / 25 mm or more. It may be greater than 1500gf / 25mm, greater than 1800gf / 25mm, or greater than 2000gf / 25mm. The higher the initial adhesive strength before UV irradiation against the glass plate, the better; however, if it is excessively high, there is a concern that sufficient peelability may not be achieved even after UV irradiation. Therefore, as an upper limit value, for example, 5000gf / 25mm or less is preferable, and it may be 4000gf / 25mm or less, or 3500gf / 25mm or less. If the initial adhesive strength before UV irradiation against the glass plate after storage under a fluorescent lamp for one day is within the above range, the surface protection film according to the embodiment of the present invention has excellent storage stability, for example. Furthermore, details of the method for measuring the initial adhesive strength before UV irradiation against the glass plate after storage under a fluorescent lamp for one day will be described later.

[0032] The surface protection film according to an embodiment of the present invention has a ratio of change from the initial adhesive strength before UV irradiation of the glass plate to the initial adhesive strength before UV irradiation of the glass plate after storage under a fluorescent lamp for one day ((initial adhesive strength before UV irradiation of the glass plate / initial adhesive strength before UV irradiation of the glass plate after storage under a fluorescent lamp) × 100 (%)) (which may be referred to as the "rate of change in initial adhesive strength before / after UV irradiation of the glass plate before storage") which is preferably 1000% or less, may be 500% or less, 200% or less, 150% or less, 130% or less, 120% or less, or 110% or less. The lower limit of the rate of change in initial adhesive strength before / after storage versus UV irradiation of the glass plate is, for example, 80% or more, 90% or more, 95% or more, or 100% or more. If the rate of change is within the above range, the surface protection film according to the embodiment of the present invention has, for example, excellent storage stability.

[0033] A surface protection film according to an embodiment of the present invention can be manufactured by any suitable method. As such a manufacturing method, for example, a known method for manufacturing a surface protection film comprising a substrate layer and an adhesive layer may be employed.

[0034] The adhesive layer included in the surface protection film according to an embodiment of the present invention may be formed by a forming method generally referred to as the "direct method" or by a forming method generally referred to as the "transfer method." The direct method is a method of forming an adhesive layer by applying an adhesive composition to a substrate layer and, if necessary, performing heating, irradiation with active energy rays (ultraviolet rays, etc.) or drying. The transfer method is a method of forming an adhesive layer by applying an adhesive composition to a release liner, etc., and, if necessary, performing heating, irradiation with active energy rays (ultraviolet rays, etc.) or drying, and transferring the formed adhesive layer to a substrate layer.

[0035] Examples of the above coating methods include gravure roll coaters, reverse roll coaters, kiss roll coaters, dip roll coaters, bar coaters, knife coaters, air knife coaters, spray coaters, comma coaters, direct coaters, roll brush coaters, etc.

[0036] The above heating or drying conditions may appropriately employ methods commonly known for the formation of an adhesive layer.

[0037] ≪A-1. Release Liner≫

[0038] As a release liner, any suitable release liner may be employed within a range that does not impair the effects of the present invention. As such a release liner, for example, a known release liner bonded to the surface of an adhesive layer included in a surface protection film may be employed. Examples of such a release liner include a release liner in which the surface of a substrate (liner substrate), such as paper or a plastic film, is silicone-treated, or a release liner in which the surface of a substrate (liner substrate), such as paper or a plastic film, is laminated with a polyolefin-based resin.

[0039] Examples of plastic films used as liner substrates include polyethylene film, polypropylene film, polybutene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polybutylene terephthalate film, polyurethane film, and ethylene-vinyl acetate copolymer film.

[0040] The thickness of the release liner is preferably 1 μm to 500 μm, may be 3 μm to 450 μm, may be 5 μm to 400 μm, or may be 10 μm to 300 μm.

[0041] ≪A-2. Adhesive Layer≫

[0042] The adhesive layer consists of an adhesive. The adhesive is formed from an adhesive composition. That is, the adhesive layer is composed of an adhesive, and the adhesive is formed from an adhesive composition. In other words, the adhesive formed from the adhesive composition constitutes a layer shape, thereby becoming an adhesive layer.

[0043] The thickness of the adhesive layer is preferably 5㎛ to 150㎛ in order to further express the effects of the present invention, and may be 10㎛ to 130㎛, 30㎛ to 120㎛, 50㎛ to 100㎛, or 60㎛ to 90㎛.

[0044] The adhesive composition comprises a urethane prepolymer (A), a crosslinking agent (B), a photopolymerization initiator (C), and an antioxidant (D). In an embodiment of the present invention, the urethane prepolymer (A), the crosslinking agent (B), the photopolymerization initiator (C), and the antioxidant (D) are used in combination as components included in the adhesive composition. Preferably, the type of each as described below is selected, or the amount used is adjusted, thereby enabling the effects of the present invention to be achieved.

[0045] <A-2-1. 우레탄 프리폴리머(A)>

[0046] The urethane prepolymer (A) corresponds to a polymer component generally referred to as a base polymer as a component of the adhesive composition.

[0047] The urethane prepolymer (A) may be of only one type or two or more types.

[0048] The content ratio of the urethane prepolymer (A) in the adhesive composition is preferably 50% to 99.9% by weight in terms of solid content, and may be 55% to 97% by weight or 60% to 95% by weight. If the content ratio of the urethane prepolymer (A) in the adhesive composition is within the above range in terms of solid content, the effects of the present invention can be further expressed.

[0049] The urethane prepolymer (A) can typically react with a crosslinking agent (B) (preferably a polyfunctional isocyanate compound) to form a urethane resin. More specifically, the urethane resin can preferably be formed from an adhesive composition containing the urethane prepolymer (A) and the crosslinking agent (B), and more specifically, the urethane resin can be formed by curing the adhesive composition containing the urethane prepolymer (A) and the crosslinking agent (B). As a method for forming the urethane resin by curing the adhesive composition containing the urethane prepolymer (A) and the crosslinking agent (B), any suitable method may be employed within a range that does not impair the effects of the present invention, such as a urethane reaction method using bulk polymerization or solution polymerization.

[0050] As is generally well known, there are two types of manufacturing methods for urethane resins: the "one-shot method," which produces a urethane resin by directly reacting a polyol with a crosslinking agent (preferably a polyfunctional isocyanate compound) without using a urethane prepolymer, and the "prepolymer method," which produces a urethane resin by reacting a urethane prepolymer with a crosslinking agent (preferably a polyfunctional isocyanate compound). In the present invention, the urethane prepolymer (A) as the base polymer corresponds to the urethane prepolymer that reacts with the crosslinking agent (preferably a polyfunctional isocyanate compound) in the "prepolymer method," and is different from the polyol that reacts with the polyfunctional isocyanate in the "one-shot method."

[0051] The number average molecular weight Mn of the urethane prepolymer (A) is preferably 3,000 to 1,000,000.

[0052] The urethane prepolymer (A) preferably comprises an alkylene oxide backbone comprising two groups selected from the group consisting of methylene groups and methine groups, and an alkylene oxide backbone comprising three or more groups selected from the group consisting of methylene groups (-CH2-) and methine groups (-CH(CH3)-), in order to exhibit the effects of the present invention. By employing the urethane prepolymer (A) having such a specific alkylene oxide backbone, the effects of the present invention can be exhibited, and, for example, sufficient strong adhesion to a substrate can be exhibited before UV irradiation, and excellent light peelability can be exhibited, allowing for smooth peeling from the substrate after UV irradiation.

[0053] The urethane prepolymer (A) may have a polymerizable unsaturated double bond. By having the urethane prepolymer (A) a polymerizable unsaturated double bond, the effects of the present invention may be further expressed. As for the polymerizable unsaturated double bond, generally known polymerizable unsaturated double bonds may be included, for example, vinyl groups, (meth)allyl groups, and (meth)acryloyl groups, and in order to further express the effects of the present invention, it is preferably a (meth)acryloyl group. The (meth)acryloyl group is at least one selected from the group consisting of acryloyl groups and methacryloyl groups.

[0054] When the urethane prepolymer (A) has polymerizable unsaturated double bonds, the content ratio of the corresponding polymerizable unsaturated double bonds in the urethane prepolymer (A) is preferably 0.10 mol / kg to 0.50 mol / kg, may be 0.15 mol / kg to 0.45 mol / kg, may be 0.20 mol / kg to 0.40 mol / kg, or may be 0.25 mol / kg to 0.35 mol / kg. If the content ratio of the polymerizable unsaturated double bonds in the urethane prepolymer (A) is within the above range, the effects of the present invention may be further expressed. If the content ratio of the polymerizable unsaturated double bonds in the urethane prepolymer (A) is too low and falls outside the above range, there is a risk that sufficient strong adhesion to the substrate may not be expressed, and, for example, there is a risk that the initial adhesion strength before UV irradiation against a glass plate may be lowered. If the content ratio of polymerizable unsaturated double bonds in the urethane prepolymer (A) is too high outside the above range, there is a risk that the peeling force will become too high in the peeling process, which is performed, for example in the manufacturing process of optical devices or electronic devices, to peel off a portion of the surface protection film attached to the substrate and expose a portion of the substrate.

[0055] In order to further express the effects of the present invention, the hydroxyl group of the urethane prepolymer (A) is preferably 2.0 KOH mg / g to 11.0 KOH mg / g, may be 4.0 KOH mg / g to 9.0 KOH mg / g, may be 5.0 KOH mg / g to 8.0 KOH mg / g, and may be 6.2 KOH mg / g to 7.0 KOH mg / g.

[0056] The urethane prepolymer (A) is preferably a polyurethane polyol.

[0057] The urethane prepolymer (A) is a polymer obtained by reacting a composition comprising, preferably, a polyol, a compound having polymerizable unsaturated double bonds, and a crosslinking agent (preferably, a polyfunctional isocyanate compound). This reaction may be carried out in the presence of a catalyst or without a catalyst.

[0058] Furthermore, in the description of the embodiments of the present invention, the term "polyol" refers to a polyol that does not contain a polymerizable unsaturated double bond. Accordingly, a compound having a polymerizable unsaturated double bond and a plurality of hydroxyl groups is considered not a "polyol" but a "compound having a polymerizable unsaturated double bond" in the description of the embodiments of the present invention.

[0059] The polyol preferably comprises at least one selected from the group consisting of polyester polyol (a1) and polyether polyol (a2).

[0060] The polyester polyol (a1) may be of only one type or two or more types.

[0061] The polyether polyol (a2) may be of only one type or two or more types.

[0062] The content of the polyol in the composition (composition comprising a polyol, a compound having a polymerizable unsaturated double bond, and a crosslinking agent) for preparing a urethane prepolymer (A) is preferably 50% to 99% by weight in terms of solid content, and may be 55% to 95% by weight or 60% to 90% by weight.

[0063] The content ratio of at least one selected from the group consisting of polyester polyol (a1) and polyether polyol (a2) among the polyols is preferably 50% to 100% by weight, may be 70% to 100% by weight, may be 80% to 100% by weight, may be 90% to 100% by weight, and may be 95% to 100% by weight.

[0064] As the polyester polyol (a1), a polyester polyol that can be normally used in the manufacture of a urethane prepolymer may be appropriately employed. Examples of such a polyester polyol (a1) include a polyester polyol obtained by reacting an acid component with a glycol component. Examples of acid components include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, and trimellitic acid. Examples of glycol components include ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, 1,6-hexane glycol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol. In addition to these, polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone), and polyvalerolactone can also be cited as polyester polyols.

[0065] As for the molecular weight of the polyester polyol (a1), it can be used from low molecular weight to high molecular weight. As for the molecular weight of the polyester polyol (a1), the number average molecular weight Mn is preferably 100 to 100000, and may be 100 to 10000.

[0066] As for the polyether polyol (a2), a polyether polyol that can be normally used in the manufacture of a urethane prepolymer may be appropriately employed. Examples of such polyether polyols (a2) include polyether polyols containing two or more functional groups, such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol (sometimes referred to as polytetramethylene ether glycol), and representative examples include polyether polyols containing two or more of at least one group selected from the group consisting of methylene groups (-CH2-) and methine groups (-CH(CH3)-). If necessary, a portion of the polyether polyol may be substituted with glycols such as ethylene glycol or polyhydric amines such as ethylenediamine and used in combination.

[0067] As for the molecular weight of the polyether polyol (a2), it can be used from low molecular weight to high molecular weight. As for the molecular weight of the polyether polyol (a2), the number average molecular weight Mn is preferably 100 to 100000, and may be 100 to 10000.

[0068] As for the polyether polyol (a2), only a difunctional polyether polyol may be used, and a polyether polyol having a number average molecular weight Mn of 100 to 100000 and having at least 3 hydroxyl groups in one molecule may be used in part or in whole.

[0069] One embodiment of the polyol is an embodiment (A) comprising both a polyester polyol (a1) and a polyether polyol (a2).

[0070] In embodiment (A), the polyether polyol (a2) is a polyether polyol comprising at least two groups selected from the group consisting of methylene groups and methine groups, for example, one or more polyether polyols (a2-1) comprising at least two groups selected from the group consisting of methylene groups and methine groups, one or more polyether polyols (a2-2) comprising at least three groups selected from the group consisting of methylene groups and methine groups, or a mixture of one or more polyether polyols (a2-1) and one or more polyether polyols (a2-2).

[0071] In embodiment (A), when the polyether polyol (a2) is a mixture of one or more types of polyether polyols (a2-1) and one or more types of polyether polyols (a2-2), the weight ratio of polyether polyol (a2-2) to 100 parts by weight of polyether polyol (a2-1) is preferably 1 part by weight to 10,000 parts by weight, and may be 5 parts by weight to 1,000 parts by weight, 8 parts by weight to 150 parts by weight, or 10 parts by weight to 100 parts by weight, in order to further express the effects of the present invention.

[0072] Polyether polyols (a2-1) comprising at least two groups selected from the group consisting of methylene groups and methine groups include, for example, polyethylene glycol and polypropylene glycol.

[0073] Polyether polyols (a2-2) comprising at least three groups selected from the group consisting of methylene groups and methine groups include, for example, polytetramethylene glycol.

[0074] In embodiment (A), when the polyether polyol (a2) is one or more of the polyether polyol (a2-1), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising at least two groups selected from the group consisting of methylene groups and methine groups.

[0075] In embodiment (A), when the polyether polyol (a2) is one or more of the polyether polyol (a2-2), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising three or more groups selected from the group consisting typically of methylene groups and methine groups.

[0076] In embodiment (A), where the polyether polyol (a2) is a mixture of one or more polyether polyols (a2-1) and one or more polyether polyols (a2-2), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising two groups selected from the group consisting of methylene groups and methine groups, typically, and an alkylene oxide backbone comprising three or more groups selected from the group consisting of methylene groups and methine groups.

[0077] In embodiment (A), the content ratio of the polyester polyol (a1) in the polyol is preferably 0.1% to 99.9% by weight, and may be 1% to 80% by weight, 5% to 60% by weight, 10% to 55% by weight, 20% to 50% by weight, or 25% to 45% by weight.

[0078] In embodiment (A), the content ratio of polyether polyol (a2) in the polyol is preferably 0.1% to 99.9% by weight, and may be 20% to 99% by weight, 40% to 95% by weight, 45% to 90% by weight, 50% to 80% by weight, or 55% to 75% by weight.

[0079] Another embodiment of the polyol is an embodiment (B) that includes a polyether polyol (a2) and does not include a polyester polyol (a1). In embodiment (B), the polyol is typically composed of a polyether polyol (a2).

[0080] In embodiment (B), the content ratio of polyether polyol (a2) in the polyol is preferably 50% to 100% by weight, and may be 70% to 100% by weight, 90% to 100% by weight, 95% to 100% by weight, or 98% to 100% by weight.

[0081] In embodiment (B), the polyether polyol (a2) is a polyether polyol comprising at least two groups selected from the group consisting of methylene groups and methine groups, for example, one or more polyether polyols (a2-1) comprising at least two groups selected from the group consisting of methylene groups and methine groups, one or more polyether polyols (a2-2) comprising at least three groups selected from the group consisting of methylene groups and methine groups, or a mixture of one or more polyether polyols (a2-1) and one or more polyether polyols (a2-2).

[0082] Polyether polyols (a2-1) comprising at least two groups selected from the group consisting of methylene groups and methine groups include, for example, polyethylene glycol and polypropylene glycol.

[0083] Polyether polyols (a2-2) comprising at least three groups selected from the group consisting of methylene groups and methine groups include, for example, polytetramethylene glycol.

[0084] In embodiment (B), when the polyether polyol (a2) is one or more of the polyether polyol (a2-1), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising at least two groups selected from the group consisting of methylene groups and methine groups.

[0085] In embodiment (B), when the polyether polyol (a2) is one or more of the polyether polyol (a2-2), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising three or more groups selected from the group consisting typically of methylene groups and methine groups.

[0086] In embodiment (B), where the polyether polyol (a2) is a mixture of one or more polyether polyols (a2-1) and one or more polyether polyols (a2-2), the urethane prepolymer (A) comprises an alkylene oxide backbone comprising two groups selected from the group consisting of methylene groups and methine groups, typically, and an alkylene oxide backbone comprising three or more groups selected from the group consisting of methylene groups and methine groups.

[0087] As for the compound having a polymerizable unsaturated double bond, any suitable compound may be used as long as it has a polymerizable unsaturated double bond and does not impair the effects of the present invention. The compound having a polymerizable unsaturated double bond may be one type or two or more types.

[0088] Examples of compounds having polymerizable unsaturated double bonds include compounds having vinyl groups, compounds having (meth)allyl groups, and compounds having (meth)acryloyl groups; preferably, in order to further express the effects of the present invention, the compounds having (meth)acryloyl groups are compounds. The number of polymerizable unsaturated double bonds in a compound having polymerizable unsaturated double bonds may be only one or two or more.

[0089] In order to further express the effects of the present invention, the content of the compound having a polymerizable unsaturated double bond in the above composition (a composition comprising a polyol, a compound having a polymerizable unsaturated double bond, and a crosslinking agent) is preferably 0.01 to 50 parts by weight per 100 parts by weight of polyol, and may be 0.1 to 30 parts by weight, 0.5 to 25 parts by weight, 1.0 to 20 parts by weight, or 1.5 to 15 parts by weight.

[0090] Examples of compounds having a (meth)acryloyl group include (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters, hydroxyl group-containing (meth)acrylic acid esters, and nitrogen atom-containing (meth)acrylic acid esters; hydroxyl group-containing (meth)acrylic acid esters are preferred in that they can further express the effects of the present invention.

[0091] As hydroxyl group-containing (meth)acrylic acid esters, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2,3-hydroxypropyl (meth)acrylate, glycerin mono(meth)acrylate, glycerin di(meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, 2-hydroxy-3-phenoxypropylacrylate, isocyanuric acid EO or PO modified (meth)acrylate, isocyanuric acid EO or PO modified di(meth)acrylate, pentaerythritol tri(meth)acrylate, Examples include dipentaerythritol penta(meth)acrylate, polypentaerythritol penta(meth)acrylate, dipentaerythritol EO or PO modified penta(meth)acrylate, dipentaerythritol caprolactone modified penta(meth)acrylate, and epoxy (meth)acrylates produced by reacting the epoxy group of an epoxy compound with the carboxyl group of (meth)acrylic acid.

[0092] Among hydroxyl group-containing (meth)acrylic acid esters, a hydroxyl group-containing (meth)acrylic acid ester having two or more hydroxyl groups is preferred in that it can further express the effects of the present invention. As for hydroxyl group-containing (meth)acrylic acid esters having two or more hydroxyl groups, glycerin mono(meth)acrylate and glycerin di(meth)acrylate are preferably examples, and commercially available products include the trade name "Blemmer GLM" (manufactured by Nichiyu Co., Ltd.), the trade name "Blemmer GLM-R" (manufactured by Nichiyu Co., Ltd.), the trade name "Blemmer GMR-M" (manufactured by Nichiyu Co., Ltd.), and the trade name "Blemmer GMR-R" (manufactured by Nichiyu Co., Ltd.).

[0093] As a crosslinking agent, any suitable crosslinking agent that can be used in the manufacture of urethane prepolymers may be employed within a range that does not impair the effects of the present invention. Preferably, such a crosslinking agent is a polyfunctional isocyanate compound. The polyfunctional isocyanate compound may be one type or two or more types.

[0094] As for the polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound may be used within a range that does not impair the effects of the present invention. Examples of such polyfunctional isocyanate compounds include polyfunctional aliphatic isocyanate compounds, polyfunctional alicyclic isocyanate compounds, polyfunctional aromatic isocyanate compounds, and polyfunctional aromatic aliphatic isocyanate compounds.

[0095] Examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, 2,3-butylene diisocyanate, dodecamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, etc.

[0096] Examples of polyfunctional cycloaliphatic isocyanate compounds include 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexanediisocyanate, 1,4-cyclohexanediisocyanate, isophorone diisocyanate, methyl-2,4-cyclohexanediisocyanate, methyl-2,6-cyclohexanediisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatomethyl)cyclohexane, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, etc.

[0097] Examples of polyfunctional aromatic isocyanate compounds include 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4',4"-triphenylmethane triisocyanate, dianisidine diisocyanate, xylylene diisocyanate, etc.

[0098] Examples of polyfunctional aromatic aliphatic isocyanate compounds include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, 1,3-tetramethylxylylene diisocyanate, etc.

[0099] Examples of polyfunctional isocyanate compounds include trimethylolpropane adducts of various polyfunctional isocyanate compounds as described above, biuret forms reacted with water, and trimers having an isocyanurate ring. In addition, these may be used in combination.

[0100] The amount of crosslinking agent that can be used to obtain a urethane prepolymer (A) is preferably 0.001 to 50 parts by weight per 100 parts by weight of polyol, and may be 0.01 to 40 parts by weight, 0.1 to 35 parts by weight, 1 to 35 parts by weight, 5 to 35 parts by weight, or 10 to 35 parts by weight.

[0101] When manufacturing the urethane prepolymer (A), a catalyst may be used. Any suitable catalyst may be used as the catalyst that can be used when manufacturing the urethane prepolymer (A). Examples of such catalysts include tertiary amine compounds and organometallic compounds. The catalyst may be of only one type or two or more types.

[0102] Examples of tertiary amine compounds include triethylamine, triethylenediamine, 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU), etc.

[0103] Examples of organometallic compounds include bismuth-based catalysts such as bismuth octylate, bismuth neodecanoate, bismuth naphthenate, and bismuth rosinate; tin-based catalysts such as dibutyltin dilaurate (DBTDL) and dioctyltin dilaurate (DOTDL); titanium-based catalysts such as dibutyl titanium dichloride, tetrabutyl titanate, butoxytitanium trichloride, and titanium tetraacetylacetonate; iron-based catalysts such as iron 2-ethylhexanate and iron acetylacetonate; cobalt-based catalysts such as cobalt benzoate and cobalt 2-ethylhexanate; zinc-based catalysts such as zinc octylate, zinc naphthenate, and zinc 2-ethylhexanate; and zirconium-based catalysts such as zirconium naphthenate.

[0104] When a catalyst is used when manufacturing a urethane prepolymer (A), the amount of catalyst used is preferably 0.0001% to 1.0% by weight with respect to the total amount of the polyol, the compound having a polymerizable unsaturated double bond, and the crosslinking agent, and may be 0.001% to 1.0% by weight, 0.003% to 1.0% by weight, or 0.005% to 1.0% by weight.

[0105] When a catalyst is used to manufacture the urethane prepolymer (A), the reaction temperature is preferably less than 100°C, and may be between 60°C and 90°C. If the temperature is 100°C or higher, there is a risk that it will be difficult to control the reaction rate and the cross-linked structure.

[0106] When manufacturing the urethane prepolymer (A), a catalyst may not be used. In this case, the reaction temperature may be 100°C or higher.

[0107] As a method for preparing a urethane prepolymer (A), examples include: 1) a method of adding the entire amount of a polyol, a compound having a polymerizable unsaturated double bond, a crosslinking agent, and a catalyst to a flask; and 2) a method of adding part or all of the polyol, part or all of the compound having a polymerizable unsaturated double bond, and a catalyst to a flask, and adding part or all of the crosslinking agent. In method 2), after adding part or all of the crosslinking agent, the remainder of the polyol, the remainder of the compound having a polymerizable unsaturated double bond, and the remainder of the crosslinking agent may be added additionally.

[0108] When manufacturing the urethane prepolymer (A), any suitable solvent may be used. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone. Among these solvents, toluene is preferably used.

[0109] When manufacturing the urethane prepolymer (A), any suitable other component may be used in any suitable amount, provided that the effects of the present invention are not impaired. Examples of other components include crosslinking promoters, silane coupling agents, antistatic agents, antioxidants, ultraviolet absorbers, light stabilizers, other resin components, tackifiers, crosslinking retardants, inorganic fillers, organic fillers, colorants (pigments or dyes, etc.), chain transfer agents, plasticizers, softeners, anti-aging agents, conductive agents, film materials, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, and lubricants. The other component may be one type or two or more types.

[0110] <A-2-2. 가교제(B)>

[0111] The urethane prepolymer (A) typically reacts with a crosslinking agent (B) to become a urethane resin. The crosslinking agent (B) may be of only one type or two or more types.

[0112] As for the crosslinking agent (B), any suitable crosslinking agent that can be used in the manufacture of urethane-based resins may be employed within a range that does not impair the effects of the present invention. Preferably, such a crosslinking agent is a polyfunctional isocyanate compound. The polyfunctional isocyanate compound may be one type or two or more types.

[0113] As a polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound that can be used in a urethane reaction may be employed. As such a polyfunctional isocyanate compound, for example, the polyfunctional isocyanate compound described above may be employed as a polyfunctional isocyanate compound that can be reacted with a polyol to obtain a urethane prepolymer (A). The polyfunctional isocyanate compound that reacts with the urethane prepolymer (A) to become a urethane-based resin may be the same as or different from the polyfunctional isocyanate compound described above as a polyfunctional isocyanate compound that can be reacted with a polyol to obtain a urethane prepolymer (A).

[0114] The equivalent ratio of the NCO group of the polyfunctional isocyanate compound to the OH group of the urethane prepolymer (A) is NCO group / OH group, preferably 0.2 to 2.9, may be 0.2 to 2.5, 0.2 to 2.0, 0.3 to 1.5, 0.3 to 1.3, 0.3 to 1.1, 0.3 to 0.9, or 0.3 to 0.7. If the equivalent ratio of the NCO group / OH group is within the above range, the effects of the present invention can be further expressed.

[0115] The content of the crosslinking agent (B) in the adhesive composition may be any appropriate amount within a range that does not impair the effects of the present invention. The content of such crosslinking agent (B) is preferably 0.3 to 13 parts by weight per 100 parts by weight of urethane prepolymer (A), and may be 0.3 to 11 parts by weight, 0.5 to 9.0 parts by weight, 0.5 to 7.0 parts by weight, 0.7 to 5.0 parts by weight, 0.7 to 3.0 parts by weight, 0.9 to 2.0 parts by weight, or 1.0 to 1.5 parts by weight. If the content of the crosslinking agent (B) per 100 parts by weight of urethane prepolymer (A) is within the above range, the effects of the present invention can be further expressed.

[0116] <A-2-3. 광중합 개시제(C)>

[0117] The adhesive composition includes a photopolymerization initiator (C). The photopolymerization initiator (C) may be one type or two or more types.

[0118] Photopolymerization initiators are generally classified into intramolecular cleavage type photopolymerization initiators and hydrogen withdrawal type photopolymerization initiators based on the reaction after absorbing light. Intramolecular cleavage type photopolymerization initiators are a type of photopolymerization initiator that generates radicals through intramolecular cleavage. For example, by absorbing light of a specific wavelength, bonds at specific sites within the molecule are cleaved, radicals are generated at the cleaved sites, and these radicals become the polymerization initiating species, thereby initiating polymerization. Hydrogen withdrawal type photopolymerization initiators are a type that generates radicals by exchanging hydrogen between two molecules. For example, by absorbing light of a specific wavelength, they become excited, and these excited species cause a hydrogen withdrawal reaction from a surrounding hydrogen donor, thereby generating an active radical species, which becomes the polymerization initiating species, thereby initiating polymerization.

[0119] Examples of intramolecular cleavage type photopolymerization initiators include alkylphenone-based photopolymerization initiators, aminoalkylphenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, or oxime ester-based photopolymerization initiators.

[0120] Examples of alkylphenone-based photoradical polymerization initiators include benzylmethylketal-based photopolymerization initiators and α-hydroxyalkylphenone-based photopolymerization initiators.

[0121] Examples of benzylmethylketal-based photopolymerization initiators include 2,2-dimethoxy-2-phenylacetophenone (commercially available, for example, Omnirad 651 (manufactured by IGM RESINS BV)).

[0122] Examples of α-hydroxyalkylphenone-based photoradical polymerization initiators include 1-hydroxycyclohexylphenylketone (commercially available, for example, Omnirad 184 (manufactured by IGM RESINS BV)), 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one.

[0123] Examples of aminoalkylphenone-based photopolymerization initiators include 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one and 2-benzylmethyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone.

[0124] Examples of acylphosphine oxide-based photopolymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (commercially available, for example, Omnirad 819 (manufactured by IGM RESINS BV)), 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, and ethyl(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0125] Examples of oxime ester-based photopolymerization initiators include (2E)-2-(benzoylyoxyimino)-1-[4-(phenylthio)phenyl]octan-1-one.

[0126] Examples of hydrogen-pulling type photopolymerization initiators include benzophenone-based photopolymerization initiators and thioxantone-based photopolymerization initiators.

[0127] Examples of benzophenone-based photopolymerization initiators include benzophenone, 4-phenylbenzophenone, o-methyl benzoylbenzoate, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone, and 4,4'-bis(dimethylamino)benzophenone.

[0128] Examples of thioxantone-based photopolymerization initiators include thioxantone, 2-chlorothioxantone, 2-methylthioxantone, 2,4-dimethylthioxantone, 2,4-diethylthioxantone, 2-isopropylthioxantone, 2,4-diisopropylthioxantone, dodecylthioxantone, and methylbenzoyl formate.

[0129] As a hydrogen drawing type photopolymerization initiator, methylbenzoyl formate (commercially available, for example, Omnirad MBF (made by IGM RESINS BV)) can also be cited.

[0130] The photopolymerization initiator (C) preferably has a maximum absorption wavelength between 310 nm and 370 nm in order to further express the effects of the present invention. If the photopolymerization initiator (C) has a maximum absorption wavelength between 310 nm and 370 nm, the effects of the present invention can be further expressed, and, for example, more sufficient strong adhesion to the substrate can be expressed before UV irradiation, and better light peelability can be expressed so that it can be smoothly peeled off from the substrate after UV irradiation.

[0131] In order to further express the effects of the present invention, the photopolymerization initiator (C) preferably has a maximum absorbance between a wavelength of 310 nm and 350 nm of 0.007 or higher when used as an acrylonitrile solution with a concentration of 0.0001 g / mL, and may also have a maximum absorbance of 0.008 or higher, 0.009 or higher, or 0.010 or higher. The upper limit of the maximum absorbance may be, for example, 0.100 or lower, or 0.050 or lower.

[0132] The content of the photopolymerization initiator (C) in the adhesive composition may be any appropriate amount within a range that does not impair the effects of the present invention. The content of such photopolymerization initiator (C) is preferably 0.001 parts by weight or more with respect to 100 parts by weight of urethane prepolymer (A), and may be 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, exceeding 0.1 parts by weight, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, exceeding 0.1 parts by weight or less, and exceeding 0.1 parts by weight or less, and less than 0.1 parts by weight or less.

[0133] <A-2-4. 산화 방지제(D)>

[0134] The adhesive composition includes an antioxidant (D). The antioxidant (D) may be one type or two or more types.

[0135] If the adhesive composition includes an antioxidant (D), the effects of the present invention may be further expressed, and, for example, storage stability may be excellent.

[0136] The content of the antioxidant (D) in the adhesive composition may be any appropriate amount within a range that does not impair the effects of the present invention. In order to further express the effects of the present invention, the content of the antioxidant (D) is preferably 0.001 parts by weight or more with respect to 100 parts by weight of the urethane prepolymer (A), and may be 0.01 parts by weight or more, 0.05 parts by weight or more, 0.10 parts by weight or more, 0.10 parts by weight to 10.00 parts by weight, 0.20 parts by weight to 5.00 parts by weight, 0.30 parts by weight to 3.00 parts by weight, or 0.40 parts by weight to 2.00 parts by weight.

[0137] A surface protection film according to an embodiment of the present invention may use a photopolymerization initiator (C) and an antioxidant (D) in combination to further express the effects of the present invention, and the ratio (weight ratio) of the content of the antioxidant (D) in the adhesive composition and the content of the photopolymerization initiator (C) in the adhesive composition (hereinafter referred to as the "antioxidant (D) / photopolymerization initiator (C) content ratio") is preferably 0.10 or higher, may be 0.15 or higher, may be 0.20 or higher, may be 0.25 or higher, may be 0.30 or higher, may be 0.35 or higher, may be 0.40 or higher, may be 0.45 or higher, and may be 0.50 or higher. The upper limit of the antioxidant (D) / photopolymerization initiator (C) content ratio is, for example, less than 10.00, less than 5.00, less than 4.00, less than 3.00, less than 2.70, and less than 2.50.

[0138] As an antioxidant (D), any suitable antioxidant may be used within a range that does not impair the effects of the present invention. Examples of such antioxidants (D) include hindered phenol-based antioxidants, hindered amine-based antioxidants, phosphite-based antioxidants, phenol-based antioxidants, and thioether-based antioxidants.

[0139] As a hindered phenolic antioxidant, for example, it may have a structure in which a tert-butyl group is bonded to at least one carbon atom adjacent to a carbon atom on an aromatic ring to which an OH group of phenol is bonded. As a hindered phenolic antioxidant, for example, dibutylhydroxytoluene (BHT); Examples of product names include Irganox 1010, Irganox 1010FF, Irganox 1035, Irganox 1035FF, Irganox 1076, Irganox 1076FD, Irganox 1076DWJ, Irganox 1098, Irganox 1135, Irganox 1330, Irganox 1726, Irganox 1425WL, Irganox 1520L, Irganox 245, Irganox 245FF, Irganox 259, Irganox 3114, Irganox 565, and Irganox 295 (all manufactured by BASF).

[0140] As a hindered amine-based antioxidant, for example, it may have at least one hindered pipericine group in one molecule. Examples of hindered amine-based antioxidants include, by trade name, Adecastab LA-63, Adecastab LA-63P, Adecastab LA-52, and Adecastab LA-57 (all manufactured by ADEKA).

[0141] Examples of phosphite-based antioxidants include triphenylphosphite, diphenylisodecylphosphite, and phenyldiisodecylphosphite; as trade names, AdekaStab 2112, AdekaStab 2112RG, AdekaStab 1178, and AdekaStab 3010 (all manufactured by ADEKA).

[0142] Examples of phenolic antioxidants include monophenolic antioxidants, bisphenolic antioxidants, and polymeric phenolic antioxidants. Examples of monophenolic antioxidants include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, and stearin-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate. Examples of bisphenol-based antioxidants include 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane. Examples of polymeric phenolic antioxidants include 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol.

[0143] Examples of thioether-based antioxidants include, for instance, Adecasteb AO-503 and Adecasteb AO-26 (both manufactured by ADEKA) as trade names.

[0144] <A-2-5. 우레탄 (메트)아크릴레이트>

[0145] The adhesive composition may include urethane (meth)acrylate. If the adhesive composition includes urethane (meth)acrylate, the effects of the present invention may be further expressed, for example, it may exhibit more sufficient strong adhesion to a substrate before UV irradiation and exhibit superior peelability that allows for smooth peeling from the substrate after UV irradiation.

[0146] Urethane (meth)acrylate may be of type 1 or type 2 or more.

[0147] In order to further express the effects of the present invention, the content of urethane (meth)acrylate in the adhesive composition is preferably 0.5 to 50 parts by weight per 100 parts by weight of urethane prepolymer (A), 1.0 to 40 parts by weight, 1.5 to 30 parts by weight, 2.0 to 20 parts by weight, 2.5 to 15 parts by weight, 3.0 to 10 parts by weight, and 3.0 to 8.0 parts by weight.

[0148] The number of functional groups of urethane (meth)acrylate is preferably 2 or more, may be 3 or more, may be 3 to 20, may be 4 to 10, may be 4 to 8, or may be 6, in order to further express the effects of the present invention. If the number of functional groups of urethane (meth)acrylate is within the above range, the effects of the present invention can be further expressed.

[0149] Urethane (meth)acrylate preferably has a structure represented by the following general formula (1) in order to further express the effects of the present invention. If the urethane (meth)acrylate has a structure represented by the following general formula (1), the effects of the present invention can be further expressed, and, for example, it can exhibit a more sufficient strong adhesion to a substrate before UV irradiation, and exhibit a more excellent peelability that allows it to be smoothly peeled off from the substrate after UV irradiation.

[0150]

[0151] Urethane (meth)acrylate preferably has a structure represented by the following general formula (1a) in order to further express the effects of the present invention. If the urethane (meth)acrylate has a structure represented by the following general formula (1a), the effects of the present invention can be further expressed, and, for example, it can exhibit a more sufficient strong adhesion to a substrate before UV irradiation, and exhibit a more excellent peelability that allows it to be smoothly peeled off from the substrate after UV irradiation.

[0152]

[0153] Urethane (meth)acrylate preferably has a structure represented by the following general formula (2) in order to further express the effects of the present invention. If the urethane (meth)acrylate has a structure represented by the following general formula (2), the effects of the present invention can be further expressed, and, for example, it can exhibit a more sufficient strong adhesion to a substrate before UV irradiation, and exhibit a more excellent peelability that allows it to be smoothly peeled off from the substrate after UV irradiation.

[0154]

[0155] In general formula (2), X is a divalent aromatic group or a divalent aliphatic group.

[0156] As for the divalent aromatic group, any suitable divalent aromatic group may be adopted within a range that does not impair the effects of the present invention. As divalent aromatic groups, for example, benzene-1,4-diyl group, benzene-1,3-diyl group, benzene-1,2-diyl group, toluene-2,4-diyl group, toluene-2,5-diyl group, toluene-2,6-diyl group, 4,6-dimethylbenzene-1,3-diyl group, 2,5-dimethylbenzene-1,4-diyl group, 2,6-dimethylbenzene-1,4-diyl group, 2,4,6-trimethylbenzene-1,3-diyl group, 2,3,5,6-tetramethylbenzene-1,4-diyl group, m-xylylene-diyl group, p-xylylene-diyl group, naphthalene-1,2-diyl group, naphthalene-1,3-diyl group, naphthalene-1,4-diyl group, Examples include naphthalene-1,5-diyl group, naphthalene-1,6-diyl group, naphthalene-1,7-diyl group, naphthalene-1,8-diyl group, naphthalene-2,3-diyl group, and naphthalene-2,6-diyl group.

[0157] As a divalent aliphatic group, any suitable divalent aliphatic group may be adopted within a range that does not impair the effects of the present invention. Examples of divalent aliphatic groups include divalent chain aliphatic groups and divalent cyclic aliphatic groups.

[0158] The divalent chain aliphatic group may be straight or branched. Examples of divalent chain aliphatic groups include the methylene group, ethane-1,1-diyl group, ethane-1,2-diyl group, propane-1,1-diyl group, propane-1,3-diyl group, propane-2,2-diyl group, pentane-1,5-diyl group, and hexane-1,6-diyl group.

[0159] Examples of divalent aliphatic groups containing a cyclic structure include, for instance, divalent aliphatic groups having a cycloalkane ring structure (e.g., a cyclohexyl ring structure). Examples of divalent aliphatic groups containing a cyclic structure include groups represented by the following general formula (3). In addition, the two bonds marked with * in general formula (3) are bonds that act as divalent groups.

[0160]

[0161] Urethane (meth)acrylate preferably has a molecular weight of less than 1000 in order to further express the effects of the present invention. If the molecular weight of urethane (meth)acrylate (D) is 1000 or more, there is a risk that the effects of the present invention may not be expressed.

[0162] As for urethane (meth)acrylates, examples include compounds having a structure represented by the following general formula (4).

[0163]

[0164] In general formula (4), X is as described above.

[0165] <A-2-6. 이온성 화합물>

[0166] The adhesive composition may include an ionic compound. The ionic compound may be just one type or two or more types.

[0167] As ionic compounds, for example, 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, 1-Methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-Methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-Ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-Octyl-3-methylimidazolium bis(fluorosulfonyl)imide, Methyltrioctylammonium bis(trifluoromethanesulfonyl)imide, Trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, Examples include 1-allyl-3-methyl-imidazolium trifluoromethanesulfonate, 1-allyl-3-methyl-imidazolium heptafluoropropanesulfonate, 1-allyl-3-methyl-imidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methyl-imidazolium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.

[0168] The content ratio of the ionic compound to 100 parts by weight of the urethane prepolymer (A) is, for example, 0.01 to 10 parts by weight, 0.03 to 7.0 parts by weight, 0.05 to 5.0 parts by weight, 0.1 to 3.0 parts by weight, 0.3 to 2.5 parts by weight, 0.5 to 2.0 parts by weight, and 0.5 to 1.5 parts by weight.

[0169] Ionic compounds may be commercially available or synthesized by any suitable method. For example, ionic liquids may be synthesized by the halide method, hydroxide method, acid ester method, complexation method, neutralization method, etc., as described in "Ionic Liquids: The Cutting Edge and Future of Development" (published by CMC Publishing).

[0170] <A-2-7. 그 밖의 성분>

[0171] The adhesive composition may include any suitable other components within a range that does not impair the effects of the present invention. Examples of such other components include solvents, catalysts, crosslinking promoters, silane coupling agents, ultraviolet absorbers, light stabilizers, other resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, colorants (pigments or dyes, etc.), chain transfer agents, plasticizers, softeners, anti-aging agents, conductive agents, thin films, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, and lubricants. The other components may be one type or two or more types.

[0172] ≪A-3. Recording Layer≫

[0173] The base layer may be just one layer, or it may be two or more layers. The base layer may be extended.

[0174] The thickness of the substrate layer is preferably 4㎛ to 450㎛, may be 8㎛ to 400㎛, 12㎛ to 350㎛, or 16㎛ to 250㎛.

[0175] For the surface of the substrate layer where the adhesive layer is not attached, for the purpose of forming a winding body that is easy to rewind, release treatment may be performed by adding, for example, fatty acid amide, polyethyleneimine, long-chain alkyl additive, etc. to the substrate layer, or a coating layer made of any suitable release agent such as silicone-based, long-chain alkyl-based, or fluorine-based agent may be provided.

[0176] An antistatic layer may be provided on the side where the adhesive layer of the substrate layer is not attached. As the antistatic layer, any suitable antistatic layer may be employed within a range that does not impair the effects of the present invention. Such an antistatic layer may include, for example, an antistatic agent. As the antistatic agent, any suitable antistatic agent may be employed within a range that does not impair the effects of the present invention. Examples of such antistatic agents include conductive polymers, carbon nanotubes, ionic compounds, carbon, surfactants, alkali metal salts, metal oxides, and metal microparticles.

[0177] As for the material of the substrate layer, any suitable material may be adopted depending on the application. Examples include plastic, paper, metal film, nonwoven fabric, etc. Preferably, it is plastic. That is, the substrate layer is preferably a plastic film. The substrate layer may be composed of one type of material or may be composed of two or more types of materials. For example, it may be composed of two or more types of plastics.

[0178] Examples of the above plastics include polyester resins, polyamide resins, polyolefin resins, etc. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.

[0179] The substrate layer may contain any suitable additives as needed. Examples of additives that may be contained in the substrate layer include antioxidants, UV absorbers, light stabilizers, antistatic agents, fillers, pigments, etc. The type, number, and amount of additives that may be contained in the substrate layer can be appropriately set according to the purpose. In particular, when the material of the substrate layer is plastic, it is desirable to contain several of the above additives for purposes such as preventing deterioration. From the perspective of improving weather resistance, antioxidants, UV absorbers, light stabilizers, and fillers are particularly preferably cited as additives.

[0180] ≪≪B. Uses≫≫

[0181] A surface protection film according to an embodiment of the present invention is typically adhered to an exposed surface of an optical member or an electronic member to prevent scratches on the surface of the optical member or electronic member during processing, assembly, inspection, transportation, etc., in a manufacturing process of an optical device or an electronic device, and can be suitably used for surface protection of the optical member or electronic member. An optical device according to an embodiment of the present invention includes an adhesive film according to an embodiment of the present invention. An electronic device according to an embodiment of the present invention includes an adhesive film according to an embodiment of the present invention.

[0182] Examples

[0183] The present invention will be specifically described below by way of examples, but the present invention is not limited in any way to these examples. Furthermore, the testing and evaluation methods in the examples, etc. are as follows. Also, where "part" is indicated, it means "parts by weight" unless otherwise specified, and where "%" is indicated, it means "% by weight" unless otherwise specified.

[0184] <Initial Adhesion to Glass Plate Before UV Irradiation>

[0185] A surface protection film (width 25 mm × length 140 mm) with the release liner peeled off was adhered to a glass plate (soda-lime glass, manufactured by Matsunami Glass High School Co., Ltd.) by one round trip of a 2 kg hand roller. Afterwards, the film was left for 30 minutes in an environment of 23°C temperature and 55%RH humidity to obtain a sample for evaluation.

[0186] The obtained evaluation sample was measured using a tensile testing machine under conditions of a temperature of 23°C and a humidity of 55%RH. As the tensile testing machine, the "Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus)" manufactured by Shimadzu Seisakusho Co., Ltd. was used. After setting the evaluation sample in the tensile testing machine, the tensile test was started. The conditions for the tensile test were set as a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load was measured when the surface protection film was peeled from the glass plate, and the average load at that time was defined as the initial adhesion strength of the surface protection film to the glass plate prior to UV irradiation.

[0187] <Initial Adhesion to Glass Plate After UV Irradiation>

[0188] A surface protection film (width 25 mm × length 140 mm) with a peeled-off release liner was adhered to a glass plate (soda-lime glass, manufactured by Matsunami Glass High School Co., Ltd.) by one round trip of a 2 kg hand roller, and then the adhesive layer was photocured by irradiating ultraviolet light with an integrated light intensity of 700 mJ / cm² using an LED light source with a wavelength of 365 nm, and then left for 30 minutes in an environment of temperature 23°C and humidity 55%RH to obtain a sample for evaluation.

[0189] The obtained evaluation sample was measured using a tensile testing machine under conditions of a temperature of 23°C and a humidity of 55%RH. As the tensile testing machine, the Shimadzu Seisakusho "Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus)" was used. After setting the evaluation sample in the tensile testing machine, the tensile test was started. The conditions for the tensile test were set as a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load was measured when the surface protection film was peeled from the glass plate, and the average load at that time was defined as the initial adhesion strength of the surface protection film against the glass plate after UV irradiation.

[0190] Magnification of change in initial adhesion strength before / after UV irradiation on glass plates

[0191] The ratio of the change in initial adhesion strength before UV irradiation to the initial adhesion strength after UV irradiation to the glass plate was defined as the ratio of the change in initial adhesion strength before / after UV irradiation to the glass plate, and was calculated by the following formula.

[0192] Ratio of change in initial adhesion strength versus glass plate before / after UV irradiation (x) = Initial adhesion strength versus glass plate before UV irradiation / Initial adhesion strength versus glass plate after UV irradiation

[0193] <Initial adhesion to glass plate before UV irradiation after 1 day of storage under fluorescent light>

[0194] After manufacturing the surface protection film, it was stored for one day under fluorescent lights in an environment of 23°C and 55%RH humidity. Subsequently, the surface protection film (width 25 mm × length 140 mm) with the release liner peeled off was adhered to a glass plate (soda-lime glass, manufactured by Matsunami Glass Co., Ltd.) by one round trip of a 2 kg hand roller. Afterward, it was left for 30 minutes in an environment of 23°C and 55%RH humidity to obtain an evaluation sample.

[0195] The obtained evaluation sample was measured using a tensile testing machine under conditions of a temperature of 23°C and a humidity of 55%RH. As the tensile testing machine, the Shimadzu Seisakusho "Autograph AG-Xplus HS 6000 mm / min high-speed model (AG-50NX plus)" was used. After setting the evaluation sample in the tensile testing machine, the tensile test was started. The conditions for the tensile test were set as a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min. The load was measured when the surface protection film was peeled from the glass plate, and the average load at that time was defined as the initial adhesion strength of the surface protection film before UV irradiation against the glass plate after storage under a fluorescent lamp for one day.

[0196] <Change in initial adhesion strength before / after storage versus glass plate before UV irradiation>

[0197] The ratio of the change from the initial adhesive strength before UV irradiation of the glass plate to the initial adhesive strength before UV irradiation of the glass plate after 1 day of storage under a fluorescent lamp was defined as the rate of change in initial adhesive strength before / after storage of the glass plate before UV irradiation of the glass plate, and was calculated by the following formula.

[0198] Percentage change in initial adhesion strength before / after storage versus glass plate before UV irradiation (%) = (Initial adhesion strength versus glass plate before UV irradiation / Initial adhesion strength versus glass plate before UV irradiation after 1 day of storage under fluorescent light) × 100 (%)

[0199] <Absorbance Measurement>

[0200] The photopolymerization initiator was diluted 10,000 times with acrylonitrile to make an acrylonitrile solution with a concentration of 0.0001 g / mL, and the maximum absorbance and maximum absorption wavelength between 310 nm and 350 nm were measured using a spectrofluorescence photometer (Hitachi Seisakusho, F-7000).

[0201] <Photopolymerization initiators used in Examples and Comparative Examples>

[0202] · Omnirad 184 (IGM Resins BV agent): Intramolecular cleavage type photopolymerization initiator, 1-hydroxycyclohexylphenyl ketone, maximum absorption wavelength = 331 nm, maximum absorbance between wavelengths 310 nm and 350 nm in acrylonitrile solution at a concentration of 0.0001 g / mL = 0.0068

[0203] · Omnirad 651 (IGM Resins BV agent): Intramolecular cleavage type photopolymerization initiator, 2,2-dimethoxy-2-phenylacetophenone, maximum absorption wavelength = 325 nm, maximum absorbance between wavelengths 310 nm and 350 nm in acrylonitrile solution at a concentration of 0.0001 g / mL = 0.0111

[0204] [Preparation Example 1] Urethane Prepolymer A

[0205] In a polymerization apparatus equipped with a 1L round-bottom separable flask, separable cover, separable lot, thermometer, dry air inlet tube, Livbit condenser, vacuum seal, stirring rod, and stirring blade, 39.1g of polytetramethylene glycol (product name "PTMG3000", manufactured by Mitsubishi Chemical Co., Ltd.), 111.9g of polyester polyol (product name "Curare Polyol P-2010", manufactured by Curare Co., Ltd.), 39.1g of a polymerizable compound having unsaturated double bonds (product name "Blemmer GLM", manufactured by Nichiyu Co., Ltd.), and 190g of toluene (manufactured by Tosho Co., Ltd.) as a solvent were added, and while stirring, 0.09g of bismuth octylate (manufactured by Nihon Kagaku Sangyo Co., Ltd.) was added as a catalyst, and dry air evacuation was carried out at room temperature for 2 hours. Subsequently, 60.5 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosho Co., Ltd.) was added, and dry air was introduced, and the solution temperature in the experimental apparatus was controlled to 80±2°C and maintained for 5 hours in a water bath. Then, 183.8 g of polypropylene glycol (product name "Sannix GP-1500", manufactured by Sanyo Kasei Co., Ltd.) was added, and the solution temperature in the experimental apparatus was controlled to 80±2°C and maintained for 2 hours in a water bath. After that, 15.4 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosho Co., Ltd.) was added, and the solution temperature in the experimental apparatus was controlled to 80±2°C and maintained for 2 hours in a water bath to obtain a solution of urethane prepolymer A. In addition, during polymerization, toluene was added dropwise in an appropriate amount to control the temperature during polymerization and to prevent a decrease in stirring ability due to an increase in viscosity. The solid content concentration of the solution of urethane prepolymer A was 60 wt%.

[0206] The formulations, etc. are shown in Table 1.

[0207] [Preparation Example 2] Urethane Prepolymer B

[0208] In a polymerization apparatus equipped with a 1L round-bottom separable flask, separable cover, separable lot, thermometer, nitrogen inlet tube, Leavitt condenser, vacuum seal, stirring rod, and stirring blade, 150.0g of polypropylene glycol (product name "Sannix PP-2000", manufactured by Sanyo Kasei Kogyo Co., Ltd.), 150.0g of polymerizable carbon double bond-containing diol (product name "Epoxyester 200PA", manufactured by Kyoesha Chemical Co., Ltd.), 272.0g of toluene as a solvent (manufactured by Tosho Co., Ltd.), 0.20g of dibutyltin(IV) dilaurate as a catalyst (manufactured by Wako Junyaku Kogyo Co., Ltd.), and 4.0g of an antioxidant (product name "Irganox 1010", manufactured by BASF) were added, and while stirring, dry air evacuation was performed at room temperature for 1 hour. Thereafter, 76.0 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosho Co., Ltd.) was added while stirring under dry air inflow, and after maintaining the solution temperature in the experimental apparatus in a water bath at 65±2℃ for 8 hours, 22.0 g of polymerizable carbon double bond containing diol (product name "Epoxyester 200PA", manufactured by Kyoesha Chemical Co., Ltd.) and 15.0 g of polymerizable carbon double bond containing triol (product name "Denacol Acrylate DA314", manufactured by Nagase Chemtex Co., Ltd.) were added, and the solution temperature in the experimental apparatus in a water bath was maintained at 65±2℃ for 8 hours to obtain a solution of urethane prepolymer B. In addition, toluene was added dropwise as needed during polymerization to control the temperature during polymerization and to prevent a decrease in stirring ability due to an increase in viscosity. The solid content concentration of the solution of urethane prepolymer B was 60 wt%.

[0209] The formulations, etc. are shown in Table 1.

[0210]

[0211] [Example 1]

[0212] Urethane prepolymer A obtained in Example 1 of preparation: 100 parts by weight, isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent: 1.4 parts by weight, Omnirad 651 (manufactured by IGM Resins BV) as a photopolymerization initiator: 0.1 parts by weight, Irganox 1010 (manufactured by BASF) as an antioxidant: 0.05 parts by weight, UA-1100H (manufactured by Shin-Nakamura Kagaku Co., Ltd.) as a urethane (meth)acrylate: 5.0 parts by weight, Envirizer OL-1 (manufactured by Tokyo Fine Chemical Co., Ltd.) as a catalyst: 0.03 parts by weight, diluted with ethyl acetate so that the total solid content is 50% by weight, and a urethane-based adhesive composition (1) was obtained.

[0213] The obtained urethane-based adhesive composition (1) was applied to a substrate made of polyester resin (product name "T100-75S", manufactured by Mitsubishi Chemical Co., Ltd., thickness 75 μm) such that the thickness after drying was 75 μm, and cured under conditions of a drying temperature of 110°C and a drying time of 3 minutes to produce an adhesive layer (1) on the substrate. Subsequently, a silicone-treated surface of a release liner made of polyester resin (product name "MRF25", manufactured by Mitsubishi Chemical Co., Ltd., thickness 25 μm), having silicone treatment on one side, was bonded to the surface of the obtained adhesive layer (1), and a surface protection film (1) was obtained with the composition of a release liner (thickness 25 μm) / adhesive layer (1) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (1) was aged at room temperature for 5 days and evaluated.

[0214] The results are shown in Table 2.

[0215] [Example 2]

[0216] Except for using 0.1 parts by weight of Omnirad 184 (IGM Resins BV) instead of 0.1 parts by weight of Omnirad 651 (IGM Resins BV) as a photopolymerization initiator, the procedure was carried out in the same manner as in Example 1 to obtain a urethane-based adhesive composition (2), a surface protection film (2) composed of a release liner (thickness 25 μm) / adhesive layer (2) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (2) was aged at room temperature for 5 days and evaluated.

[0217] The results are shown in Table 2.

[0218] [Example 3]

[0219] Except for changing the amount of antioxidant (Irganox 1010) to 0.10 parts by weight, the same procedure as in Example 1 was performed to obtain a urethane-based adhesive composition (3), a surface protection film (3) composed of a release liner (thickness 25 μm) / adhesive layer (3) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (3) was aged at room temperature for 5 days and evaluated.

[0220] The results are shown in Table 2.

[0221] [Example 4]

[0222] Except for changing the amount of photopolymerization initiator (Omnirad 651) to 0.5 parts by weight, the same procedure as in Example 3 was performed to obtain a urethane-based adhesive composition (4), a surface protection film (4) composed of a release liner (thickness 25 μm) / adhesive layer (4) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (4) was aged at room temperature for 5 days and evaluated.

[0223] The results are shown in Table 2.

[0224] [Example 5]

[0225] Except for changing the amount of antioxidant (Irganox 1010) to 0.50 parts by weight, the same procedure as in Example 4 was performed to obtain a urethane-based adhesive composition (5), a surface protection film (5) composed of a release liner (thickness 25 μm) / adhesive layer (5) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (5) was aged at room temperature for 5 days and evaluated.

[0226] The results are shown in Table 2.

[0227] [Example 6]

[0228] Except for changing the amount of antioxidant (Irganox 1010) to 1.50 parts by weight, the same procedure as in Example 5 was performed to obtain a urethane-based adhesive composition (6), a surface protection film (6) composed of a release liner (thickness 25 μm) / adhesive layer (6) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (6) was aged at room temperature for 5 days and evaluated.

[0229] The results are shown in Table 2.

[0230] [Example 7]

[0231] Except for not using urethane (meth)acrylate (UA-1100H), the same procedure as in Example 5 was performed to obtain a urethane-based adhesive composition (7), a surface protection film (7) composed of a release liner (thickness 25 μm) / adhesive layer (7) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (7) was aged at room temperature for 5 days and evaluated.

[0232] The results are shown in Table 2.

[0233] [Comparative Example 1]

[0234] Except for not using an antioxidant (Irganox 1010), the same procedure as in Example 5 was performed to obtain a urethane-based adhesive composition (C1), a surface protection film (C1) composed of a release liner (thickness 25 μm) / adhesive layer (C1) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (C1) was aged at room temperature for 5 days and evaluated.

[0235] The results are shown in Table 2.

[0236] [Comparative Example 2]

[0237] A urethane-based adhesive composition (C2) was prepared in the same manner as in Example 1, except that 100 parts by weight of the urethane prepolymer B obtained in Example 2 was used instead of 100 parts by weight of the urethane prepolymer A obtained in Example 1, the amount of the crosslinking agent (C / HX) was changed to 5.0 parts by weight, the amount of the photopolymerization initiator (Omnirad 651) was changed to 1.0 part by weight, the amount of the antioxidant (Irganox 1010) was changed to 1.00 parts by weight, and the urethane (meth)acrylate (UA-1100H) was not used, and a surface protection film (C2) was obtained having a composition of a release liner (thickness 25 μm) / adhesive layer (C2) (thickness 75 μm) / substrate (thickness 75 μm). The obtained surface protection film (C2) was aged at room temperature for 5 days and evaluated.

[0238] The results are shown in Table 2.

[0239] Industrial applicability

[0240] The surface protection film of the present invention can be used for any suitable application. Preferably, the surface protection film of the present invention is preferably used in the field of optical devices or electronic devices. Explanation of the symbols

[0241] 1: Base layer 2: Adhesive layer 10: Surface protection film

Claims

Claim 1 A surface protection film comprising an adhesive layer, wherein the adhesive constituting the adhesive layer is formed as an adhesive composition, and the adhesive composition comprises a urethane prepolymer (A), a crosslinking agent (B), a photopolymerization initiator (C), and an antioxidant (D), wherein the urethane prepolymer (A) comprises an alkylene oxide backbone comprising two groups selected from the group consisting of methylene groups and methine groups, and an alkylene oxide backbone comprising three or more groups selected from the group consisting of methylene groups and methine groups. Claim 2 A surface protection film according to claim 1, wherein the amount of the antioxidant (D) per 100 parts by weight of the urethane prepolymer (A) is 0.10 parts by weight or more. Claim 3 A surface protection film according to claim 1, wherein the ratio of the amount of the antioxidant (D) to the amount of the photopolymerization initiator (C) (antioxidant (D) / photopolymerization initiator (C)) is 0.25 or more by weight. Claim 4 A surface protection film according to claim 1, wherein the ratio of the amount of the antioxidant (D) to the amount of the photopolymerization initiator (C) (antioxidant (D) / photopolymerization initiator (C)) is less than 3.00 by weight. Claim 5 A surface protection film according to claim 1, wherein the amount of the photopolymerization initiator (C) per 100 parts by weight of the urethane prepolymer (A) exceeds 0.1 parts by weight. Claim 6 A surface protection film according to claim 1, wherein the adhesive composition comprises urethane (meth)acrylate. Claim 7 An optical device comprising a surface protection film described in any one of claims 1 to 6. Claim 8 An electronic device comprising a surface protection film described in any one of claims 1 to 6.